Understanding the mechanisms of stress corrosion cracking - Kruska, K (2012)
Austenitic stainless steels are frequently used in the cooling circuits of nuclear reactors. It has been found that cold-worked 304 stainless steels can be particularly susceptible to stress corrosion cracking at the operating conditions of such reactors. Despite more than 130 years of research underlying mechanisms are still not properly understood. For this reason, the effects of cold-work and applied stress on the oxidation behaviour of 304SS have been studied in this thesis. A set of samples with/without prior cold-work, and with/without stress applied during oxidation, were oxidized in autoclaves under simulated pressurised water reactor primary circuit conditions. Atom-probe tomography and analytical transmission electron microscopy were used to investigate the local chemistry and microstructure in the different samples tested. Regions containing grain boundaries, deformation bands, and matrix material in contact with the environment, were extracted from the coupon specimens with a focused ion beam machine. Cross-sections of crack tips were studied with secondary ion mass spectrometry and electron backscatter diffraction. The compositions of oxides grown along the surface and the different microstructural features were analysed. Fe-rich spinels were found at the surface and Cr-rich spinels were observed along fast diffusion paths. Ni-enrichment was found at the metal/oxide interfaces and a Ni-rich phase was detected in precipitates ahead of grain boundary oxides. Li was observed in all oxidised regions and B segregation, originating from impurities in the alloy, was observed in grain boundaries and crack tip oxides. Cavities and hydrogen associated with Ni-rich regions were found ahead of the bulk Cr-rich oxide in some of the samples. The implications of these findings for the understanding of SCC mechanisms are discussed. It is suggested that Ni precipitation as well as the presence of deformation bands may play an important role in controlling SCC susceptibility in 304 stainless steel. A modification of the film-rupture model including internal oxidation and fast diffusion along H-stabilised vacancies in strain fields at the crack front is proposed.